Thermo-optical characterization of tellurite glasses by thermal lens, thermal relaxation calorimetry and interferometric methods - Lima, S. M.; Falco, W. F.; Bannwart, E. S.; Andrade, L. H. C.; de Oliveira, R. C.; Moraes, João Carlos Silos [UNESP]; Yukimitu, K.; Araujo, E. B.; Falcao, E. A.; Steimacher, A.; Astrath, N. G. C.; Bento, A. C.; et al. (Elsevier B.V., 2006)
In this work the thermal lens, thermal relaxation calorimetry and interferometric methods are applied to investigate the thermo-optical properties of tellurite glasses (in mol%: 80TeO(2)-20 Li2O(TeLi), 80TeO(2)-15Li(2)O-5TiO(2) (TeLiTi-5) and 80TeO(2)-10Li(2)O-10TiO(2) (TeLiTi-10)). Thermal diffusivity, thermal conductivity, specific heat and the temperature coefficients of refractive index, optical path length, thermal expansion and electronic polarizability were determined. The use of three independent methods was useful for a complete characterization of the studied tellurite glasses. In addition, our results showed that the thermal expansion coefficient and the temperature coefficient of the optical path length (dS/dT) were significantly modified with the introduction of titanium, which may be relevant for the application of these glasses in the photonic area. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: tellurites; thermal properties; thermal conductivity